Investigation into calibration performance of small volume prover for hydrocarbon flow. (March 2015) - Shimada, Takashi; Doihara, Ryouji; Terao, Yoshiya
Abstract: Several kinds of commercial flowmeters, namely, Coriolis flowmeters, turbine meters, ultrasonic flowmeters, and positive displacement flowmeters, have been calibrated using the primary standard for hydrocarbon flow measurement in Japan (which is based on static and gravimetric methods with a flying start and finish) and a small volume prover (SVP) at the same calibration condition in order to investigate the performance of the SVP. The differences in calibration results for the mechanical flowmeters between the primary standard and the SVP apparently depend on the flow rate, although the results show agreement within 0.04%. The computer-based flowmeters, which have a time delay in the output pulse signal, indicated larger differences due to the effect of the sudden flow rate change caused by the proving action of the SVP at larger flow damping times. Highlights: We investigate the calibration performance of an SVP with a piston valve. We calibrate several kinds of flowmeters using the primary standard and the SVP. K factors using the SVP are dependent on the flow rates. Some computer-based flowmeters are affected by the proving action of the SVP.